Brain signatures of threat–safety discrimination in adolescent chronic pain. Issue 3 (March 2020) - Heathcote, Lauren C.; Timmers, Inge; Kronman, Corey A.; Mahmud, Farah; Hernandez, J. Maya; Bentley, Jason; Youssef, Andrew M.; Pine, Daniel S.; Borsook, David; Simons, Laura E.
Abstract : Abstract: Approximately 1.7 million youth suffer from debilitating chronic pain in the US alone, conferring risk of continued pain in adulthood. Aberrations in threat–safety (T–S) discrimination are proposed to contribute to pain chronicity in adults and youth by interacting with pain-related distress. Yet, few studies have examined the neural circuitry underlying T–S discrimination in patients with chronic pain or how T–S discrimination relates to pain-related distress. In this study, 91 adolescents (10-24 years; 78 females) including 30 chronic pain patients with high pain-related distress, 29 chronic pain patients with low pain-related distress, and 32 healthy peers without chronic pain completed a developmentally appropriate T–S learning paradigm. We measured self-reported fear, psychophysiology (skin conductance response), and functional magnetic resonance imaging responses (N = 72 after functional magnetic resonance imaging exclusions). After controlling for age and anxiety symptoms, patients with high pain-related distress showed altered self-reported fear and frontolimbic activity in response to learned threat and safety cues compared with both patients with low pain-related distress and healthy controls. Specifically, adolescent patients with high pain-related distress reported elevated fear and showed elevated limbic (hippocampus and amygdala) activation in response to a learned threat cue (CS+). In addition, they showed decreased frontal (vmPFC) activation and aberrant frontolimbic connectivity in response to a learned safety cue (CS−). Patients with low pain-related distress and healthy controls appeared strikingly similar across brain and behavior. These findings indicate that altered T–S discrimination, mediated by frontolimbic activation and connectivity, may be one mechanism maintaining pain chronicity in adolescents with high levels of pain-related distress. Abstract : Supplemental Digital Content is Available in the Text.Adolescent chronic pain patients with high pain-related distress show altered frontolimbic brain reactivity when processing learned threat and safety cues.